If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -8x) = -275 (1 * 5 + -8x * 5) = -275 (5 + -40x) = -275 Solving 5 + -40x = -275 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -40x = -275 + -5 Combine like terms: 5 + -5 = 0 0 + -40x = -275 + -5 -40x = -275 + -5 Combine like terms: -275 + -5 = -280 -40x = -280 Divide each side by '-40'. x = 7 Simplifying x = 7
| 6(6r-5)=-205 | | -115=-3-8(m+8) | | 5(3+y)= | | 5k+5k^2=0 | | 96=6(6n-8) | | U^2+20u+19=0 | | 8m+4m-12=24 | | 129=-6(3+7m)-7m | | 18x-(x-4)+6(3x+8)= | | 3ln(x-3)=15 | | 7-7a=2-6a | | ln(x+1)-ln(2x-3)=0 | | (-7x-3)-5=190 | | 6d^2-3d=0 | | 2-3(5b-3)=-109 | | w(w+2)=11 | | 18x-(x-4)+(3x+8)= | | 7n-3=7n+2 | | 3-(3-x)+6= | | 224=14x | | 0,3x+0,6=2,6+0,6x-0,6 | | 7+4n=-6+6 | | (4n+3)(4n+1)= | | X^2-8=6x | | 3x+3-x+2= | | 166=8h+13g | | 4f-6f^2=0 | | 1gx=3 | | x+2+x+6=288 | | 0.5z=9.25 | | (5x)+3=8 | | 4x-84=80 |